2013
DOI: 10.7785/tcrt.2012.500332
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hematologic and Mucosal Toxicities in Head and Neck Cancer Patients Undergoing Chemoradiotherapy: A Comparison of 3D-CRT, IMRT, and Helical Tomotherapy

Abstract: IMRT and helical tomotherapy for head and neck cancer (HNC) treatment are associated with higher doses to certain non-target tissues than traditional static beam techniques. We hypothesized that this may lead to higher acute mucosal and hematologic toxicities. This analysis was limited to 178 patients receiving ≥ 60 Gy with concurrent weekly cisplatin. Radiation delivery used 3D-CRT in 41 patients (23%), conventional IMRT in 56 patients (31%), and helical tomotherapy in 81 patients (46%). Acute mucositis rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
3
14
2
Order By: Relevance
“…However, key literature available for comparison has been outlined in Table 4, and data available suggests similarities between the current data and prior helical IMRT results. 35,37,38,45 Similarly, grade 2 rates also had substantial variation ranging from 30%-90% 38,45 with the current study results falling in the mid-range for both grades. 35,37,38,45 Similarly, grade 2 rates also had substantial variation ranging from 30%-90% 38,45 with the current study results falling in the mid-range for both grades.…”
Section: Comparison With Existing Helical Intensity-modulated Radiosupporting
confidence: 59%
See 3 more Smart Citations
“…However, key literature available for comparison has been outlined in Table 4, and data available suggests similarities between the current data and prior helical IMRT results. 35,37,38,45 Similarly, grade 2 rates also had substantial variation ranging from 30%-90% 38,45 with the current study results falling in the mid-range for both grades. 35,37,38,45 Similarly, grade 2 rates also had substantial variation ranging from 30%-90% 38,45 with the current study results falling in the mid-range for both grades.…”
Section: Comparison With Existing Helical Intensity-modulated Radiosupporting
confidence: 59%
“…Specifically, the low rate of long-term gastrostomy use (>12 months) was comparable to the rates reported by Nguyen et al 37 and Kimura et al 35 Oral mucositis data is the only other acute toxicity available for comparison, however, across the studies that have reported results, the incidence of grade 3 mucositis varies widely from 0%-72%. 35,37,38,45 Similarly, grade 2 rates also had substantial variation ranging from 30%-90% 38,45 with the current study results falling in the mid-range for both grades. Dysphagia outcomes have only been reported in 1 helical IMRT study to date.…”
Section: Comparison With Existing Helical Intensity-modulated Radiosupporting
confidence: 59%
See 2 more Smart Citations
“…For example, high‐dose head and neck radiation typically causes mild injury in most patients when the oral mucosal tissue is exposed to at least 1500–2000 cGy; moderate‐to‐severe mucositis then predictably occurs as the radiation dose approaches and exceeds 5000 cGy. Intensity‐modulated radiation therapy (IMRT), although associated with higher doses to selected non‐target tissue vs static beam techniques, does not appear to cause increased acute mucosal toxicity (Kruser et al , ). High‐dose chemotherapy can cause oral mucositis ranging in severity from mild to severe, as is the case with gastrointestinal mucositis as well.…”
Section: Observations From the Clinical Sector: Valuable Cluesmentioning
confidence: 99%